Political and Cultural Inclusion in Nepal - Paudel, Minraj (JMC Research Journal, 2020)
Political and social inclusion refers to political participation at different levels of the power structure and the language, religion, social habits, and knowledge of a particular group of people. The review of the literature method is used in the study. The study aims to analyze the political and cultural inclusion and their implementation status in Nepal. The secondary data have been studied by textual, average, percentage, and number. It is found that the constitution of Nepal has given equal rights to everyone and provided special quotas for women and others led to federal to local governments and has managed different fundamental rights. On the other hand, it is seen that no cultural provisions in implemented practices. The women present are 37.33 percent, 40.75 percent, and 16.02 percent in NA, HoR, and PA, in local governments, and in political parties' central committees, respectively. Political and social inclusion indicates the political participation at different levels of the power structure and the language, religion, social habits, and knowledge of a particular group of people. The review of the literature method is used in the study. This study analyzes the political and cultural inclusion and its implementation status in Nepal. The secondary data has been studied, and these data have been analyzed by text, average, percentage, and number. Nepal's constitution has given everyone equal rights, provided special quotas for women and others, led federal to local governments, and managed different fundamental rights. On the other hand, it is seen that no cultural provisions have been implemented in practice. The women present are 37.33 percent, 40.75 percent, and 16.02 percent in NA, HoR, and PA, in local governments, and in political parties' central committees, respectively.